Solid Tumor-Targeting Theranostic Polymer Nanoparticle in Nuclear Medicinal Fields - Akira Makino; Shunsaku Kimura (The Scientific World Journal)
Polymer nanoparticles can be prepared by self-assembling of amphiphilic polymers, and various types of molecular assemblies have been reported. In particular, in medicinal fields, utilization of these polymer nanoparticles as carriers for drug delivery system (DDS) has been actively tried, and some nanoparticulate drugs are currently under preclinical evaluations. A radionuclide is an unstable nucleus and decays with emission of radioactive rays, which can be utilized as a tracer in the diagnostic imaging systems of PET and SPECT and also in therapeutic purposes. Since polymer nanoparticles can encapsulate most of diagnostic and therapeutic agents with a proper design of amphiphilic polymers, they should be effective DDS carriers of radionuclides in the nuclear medicinal field. Indeed, nanoparticles have been recently attracting much attention as common platform carriers for diagnostic and therapeutic drugs and contribute to the development of nanotheranostics. In this paper, recent developments of solid tumor-targeting polymer nanoparticles in nuclear medicinal fields are reviewed.